2012
DOI: 10.3892/mmr.2015.3519
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of valproic acid and arsenic trioxide on RPMI8226 cells in vitro and the possible underlying mechanisms

Abstract: Abstract. The aim of the present study was to investigate the synergistic effects of valproic acid (VPA) and arsenic trioxide (ATO) on the proliferation of RPMI8226 cells and the possible underlying mechanisms. Cell apoptosis was assessed by flow cytometry. The mRNA expression levels were analyzed by semi-quantitative polymerase chain reaction, and the protein expression levels were analyzed by western blotting. The histone acetylation and methylation states of the gene promoters were detected using a chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Studies have demonstrated that arsenic compounds could only activate the caspase-8 pathway to induce human melanoma cell apoptosis by enhancing TRAIL-induced apoptosis with the suppression of the NF-κB and STAT3-transcriptional targets (59) and could only stimulate the caspase-9 pathway to induce liver cancer cell apoptosis by downregulating phosphorylated-STAT3 expression with Bcl-2, XIAP, and surviving proteins (60), respectively. Studies have also revealed that arsenic compounds could activate both the caspase-8 and caspase-9 pathways concurrently to induce myeloma and promonocytic leukemia cell apoptosis by decreasing the expression of Bcl-2 families and/or regulating p38-MAPK process (61,62). In the present study, NaAsO 2 and DMA could concurrently induce both the caspase-8 and -9 pathways in OEC-M1 cells, indicating that our observations are not unprecedented.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Studies have demonstrated that arsenic compounds could only activate the caspase-8 pathway to induce human melanoma cell apoptosis by enhancing TRAIL-induced apoptosis with the suppression of the NF-κB and STAT3-transcriptional targets (59) and could only stimulate the caspase-9 pathway to induce liver cancer cell apoptosis by downregulating phosphorylated-STAT3 expression with Bcl-2, XIAP, and surviving proteins (60), respectively. Studies have also revealed that arsenic compounds could activate both the caspase-8 and caspase-9 pathways concurrently to induce myeloma and promonocytic leukemia cell apoptosis by decreasing the expression of Bcl-2 families and/or regulating p38-MAPK process (61,62). In the present study, NaAsO 2 and DMA could concurrently induce both the caspase-8 and -9 pathways in OEC-M1 cells, indicating that our observations are not unprecedented.…”
Section: Discussionsupporting
confidence: 58%
“…In the present study, NaAsO 2 and DMA could concurrently induce both the caspase-8 and -9 pathways in OEC-M1 cells, indicating that our observations are not unprecedented. It is well known that up-and downstream of the caspase-8 and -9 pathways, pathways including Fas/Fas ligand, BCL-2, ER stress, and/or p53, are markedly involved with the finer regulation of cancer cell apoptosis (59)(60)(61)(62). Thus, it is worth further investigating how caspase-8 and -9 pathways are regulated by up-and downstream regulators to induce OEC-M1 cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical studies have shown that ATO in combination with (i) signalling inhibitors, including recombinant mutant human TRAIL (Zhou et al , ), PD184352 (Lunghi et al , ), and sulforaphane (SFN) (Doudican et al , ); (ii) oxidative stress pathway modulators [such as AA (Bahlis et al , )]; and (iii) therapeutic drugs [MEL, BTZ (Wen et al , ), imatinib, 5‐azacytidine (Chen et al , ), valproic acid (Wang & Zhang, ) and ATRA] exhibits synergistic anti‐MM activity both in vitro and in vivo . Our previous study shows that SFN, a dietary isothiocyanate found in cruciferous vegetables, has anti‐MM activity associated with induction of apoptosis (Jakubikova et al , ).…”
Section: Discussionmentioning
confidence: 99%